Colorectal surgery - Bailey, H. Randolph; Billingham, Richard P; Stamos, Micheal J; Snyder, Micheal J (Elsevier/Saunders, 2013)
Colorectal Surgery equips you to overcome the clinical challenges you face in this area of surgery. Written for the general surgeon who is called upon to manage diseases and disorders of the large bowel, rectum, and anus, this reference provides advanced, expert guidance on how to avoid complications and achieve the most successful results.Visualize relevant anatomy and techniques more easily with high-quality, full-color line drawings and clinical photos throughout.Zero in on the information you need with key points boxes in every chapter that provide a quick overview of the topic at hand.Get practical, hands-on advice on managing the diseases and disorders you're most likely to encounter.Learn from acknowledged leaders in the field who excel in both academic and clinical areas.Access the searchable contents online at www.expertconsult.com, along with downloadable images of key surgical techniques.